Blended learning in elementary school science learning: A systematic literature review - Herwulan Irine Purnama; Insih Wilujeng; Cepi Safruddin Abdul Jabar (International Journal of Evaluation and Research in Education (IJERE), 2023)
This article presents a systematic literature review (SLR) on blended learning in elementary school science learning. The method used is SLR and PRISMA protocol with the stages of identification, screening, eligibility, inclusion, abstraction, and data analysis assisted by Publish or Perish 7, Mendeley, VOSviewer, and NVIVO 12 Plus applications. The findings in Scopus found 906 articles, and then filtered them according to compatible themes into 54 pieces. The topic findings were blended learning, science learning, elementary school, the concept of blended learning, type of blended learning, the impact of blended learning, flipped learning, flip classroom, distance learning, distance education, active learning, online learning, blended and face-to-face learning, STEM, which were directly and indirectly connected. The 54 articles were analyzed according to the defined topics through NVIVO 12 Plus, and the results were described according to the research questions. The research findings explain that blended learning in elementary school science learning is a mixed learning model with the integration of synchronous-asynchronous technology, information, and communication technology (ICT), technological pedagogical content knowledge (TPACK), multimedia, and Android from planning to evaluation. The most studied type of blended learning is the flipped classroom, with as many as 11 studies. The implementation of blended learning has more positive impacts on students and teachers. Future research needs to explore blended learning in elementary school science learning and what students, teachers, and technological developments need.